Pemahaman Masyarakat Terhadap Ayat-Ayat Adopsi Anak - Hasibuan, Nurhidayah; Hasiah, Hasiah (Jurnal El-Thawalib, 2022)
The Focus of this research is public understanding of the verses about child adoption in the Lubuk Barumun District, Padang Lawas Regency, with two problems, namely 1) haw to implement child adopsion in Lubuk barumun District Padang Lawas Regency, and 2) haw to public understanding  of the verses about child adoption. This research that uses data collection techhniques, namely with observation, interviews, and documentation. Then take books related to this research such as jurnals, goverment publication, as well as other sites or sources that suppor this research. The results of this study indicate that the implementation of child adoption that occurs in the Lubuk Barumun District community is giving ransom to biological parents and helping relatives who cannot afford to pay for their children. There are several reasons why families adopt in Lubuk Barumun District, namely to make the adopted child their biological child and result in the child's blood relationship. And the family adopted a child because they had been married for a long time and had no children. There is also a reason that because of economic factors and because they do not have a son, so they are interested in adopting a boy with the aim of provoking the birth of a boy in their family. The understanding of the people of Lubuk Barumun District, Padang Lawas Regency regarding the verses about child adoption is that it is permissible to adopt a child but not to lose the original lineage. You may adopt a child but you may not be a guardian in your adopted child's marriage. You can adopt children but you can't inherit each other.